2009
DOI: 10.1111/j.1365-2958.2009.06795.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biochemical analyses of the Pseudomonas aeruginosa Psl exopolysaccharide reveal overlapping roles for polysaccharide synthesis enzymes in Psl and LPS production

Abstract: Exopolysaccharides contribute significantly to attachment and biofilm formation in the opportunisitc pathogen Pseudomonas aeruginosa. The Psl polysaccharide, which is synthesized by the polysaccharide synthesis locus (psl), is required for biofilm formation in nonmucoid strains that do not rely on alginate as the principal biofilm polysaccharide. In-frame deletion and complementation studies of individual psl genes revealed that eleven psl genes, pslACDEFGHIJKL, are required for Psl production and surface atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
403
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 342 publications
(431 citation statements)
references
References 65 publications
10
403
3
5
Order By: Relevance
“…Addition of 2% arabinose decreased the biofilm biomass of PAO1/pHERD20T-pslG to a level similar to ΔpslG mutant (Supplementary information, Table S1 and Figure 1A). In contrast, the biofilm biomass was increased in Psl-inducible strain WFPA801 (psl promoter was replaced by araC-P BAD , Supplementary information, Table S1) due to elevated Psl production (Figure 1A), where the entire psl gene operon was induced by the P BAD promoter [20,23]. Given that the growth of PAO1 was not affected by PslG expression and arabinose concentration (Supplementary information, Figure S1A), these results suggested that the overexpression of PslG might decrease the production of Psl in PAO1.…”
Section: Overexpression Of Pslg Inhibited Biofilm Formation Of P Aermentioning
confidence: 95%
See 4 more Smart Citations
“…Addition of 2% arabinose decreased the biofilm biomass of PAO1/pHERD20T-pslG to a level similar to ΔpslG mutant (Supplementary information, Table S1 and Figure 1A). In contrast, the biofilm biomass was increased in Psl-inducible strain WFPA801 (psl promoter was replaced by araC-P BAD , Supplementary information, Table S1) due to elevated Psl production (Figure 1A), where the entire psl gene operon was induced by the P BAD promoter [20,23]. Given that the growth of PAO1 was not affected by PslG expression and arabinose concentration (Supplementary information, Figure S1A), these results suggested that the overexpression of PslG might decrease the production of Psl in PAO1.…”
Section: Overexpression Of Pslg Inhibited Biofilm Formation Of P Aermentioning
confidence: 95%
“…Deletion of pslG led to loss of Psl production and reduction of biofilm formation in P. aeruginosa PAO1 strain [23]. However, the biofilm biomass was significantly reduced in PAO1/pHERD20T-pslG, where expression of the full-length PslG was driven by P BAD promoter in plasmid pHERD20T and was induced by arabinose.…”
Section: Overexpression Of Pslg Inhibited Biofilm Formation Of P Aermentioning
confidence: 99%
See 3 more Smart Citations